2021
DOI: 10.4314/as.v20i1.15
|View full text |Cite
|
Sign up to set email alerts
|

Manurial amendments and source of water for supplemental irrigation of sawah-rice system influenced soil quality and rice yield

Abstract: Soil and water management research on adapting the promising sawah ecotechnology for lowland rice farming in West Africa has largely focused on the abundant inland valleys; floodplains which too represent a huge agricultural resource in the region have not been so involved. Sawah refers to a bunded, puddled and leveled basin for rice, with water inlets and outlets for irrigation and drainage, respectively. In conventional sawah, soil fertility is augmented using mineral fertilizers, with an option to harness l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…Agricultural potentials of alluvial soils have not been fully exploited due to insufficient data on their physical and chemical properties and concomitant changes they undergo under intensive cultivation (Effiong and Ibia, 2009;Ukaegbu et al, 2015;Ukabiala et al, 2021). Floodplains are about the most fertile lowland resources used mostly for rice production as well as dry season vegetable farming, and they can be highly responsive to management (Nnadi et al, 2021). In Bayelsa State of Nigeria occurs a vast land space of floodplain soils with high agricultural potentials but current information on their characteristics, capabilities and suitability are inadequate (Dickson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Agricultural potentials of alluvial soils have not been fully exploited due to insufficient data on their physical and chemical properties and concomitant changes they undergo under intensive cultivation (Effiong and Ibia, 2009;Ukaegbu et al, 2015;Ukabiala et al, 2021). Floodplains are about the most fertile lowland resources used mostly for rice production as well as dry season vegetable farming, and they can be highly responsive to management (Nnadi et al, 2021). In Bayelsa State of Nigeria occurs a vast land space of floodplain soils with high agricultural potentials but current information on their characteristics, capabilities and suitability are inadequate (Dickson et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The increasing request for high-quality water for irrigation in Rwanda in the last years has led to the use of poor-quality water for irrigation mainly in farmland. The use of low-quality water could cause a decline in crop productivity (Nwite et al, 2017;Abdel-Fattah et al, 2020;Nnadi et al, 2021). The current study indicated that the water of the Kanzenze River was classified as moderate for salinity and acidic hazard.…”
Section: Discussionmentioning
confidence: 72%
“…Lowest mean SOC was observed on A -LU3 at Ado-Ekiti. This may be attributed to frequent wetting-drying cycles in waterlogged soils which facilitates SOC decomposition, thus lowering of its content in the soil (Nwite et al, 2017;Nnadi et al, 2021). At the two sites, the range of mean SOM among the LUTs and across the four soil depths ranged between 0.60 and 1.56% and 0.59 and 1.59% respectively.…”
Section: Soil Chemical Propertiesmentioning
confidence: 98%